Autosomal Dominant Alzheimer Disease: A Unique Resource to Study CSF Biomarker Changes in Preclinical AD - Schindler, Suzanne Elizabeth; Fagan, Anne M. (Frontiers in Neurology, 2015)
Our understanding of the pathogenesis of Alzheimer disease (AD) has been greatly influenced by investigation of rare families with autosomal dominant mutations that cause early onset AD. Mutations in the genes coding for Amyloid Precursor Protein (APP), Presenilin 1 (PSEN-1) and Presenilin 2 (PSEN-2) cause over-production of the amyloid-beta peptide (Abeta) leading to early deposition of Abeta in the brain, which in turn is hypothesized to initiate a cascade of processes resulting in neuronal death, cognitive decline and eventual dementia. Studies of cerebrospinal fluid (CSF) from individuals with the more common late-onset form of AD (LOAD) has revealed that low CSF Abeta42 and high CSF tau are associated with AD brain pathology. Herein we review the literature on CSF biomarkers in autosomal dominant AD (ADAD) which has contributed to a detailed road map of AD pathogenesis, especially during the preclinical period, prior to the appearance of any cognitive symptoms. Current drug trials are also taking advantage of the unique characteristics of ADAD and utilizing CSF biomarkers to accelerate development of effective therapies for AD.